1973
DOI: 10.1515/zna-1973-0507
|View full text |Cite
|
Sign up to set email alerts
|

Normale und anomale Absorption von Röntgen-Strahlen in Germanium und Silicium/Normal and anomalous absorption of X-rays in Germanium and Silicon

Abstract: N o r m a le u n d a n o m a le A b s o r p tio n v o n R ö n tg e n -S tr a h le n in G e r m a n iu m u n d S iliciu m Normal and anomalous absorption of X-rays in Germanium and Silicon A brief discussion of G. Moliere's generalized dynamical theory is given with respect to the interpretation of the experimental data ! % 1,/Z-o I obtained by means of the Borrmann effect.In order to compare theory and experiment photoelectric absorption cross sections for Silicon and Germanium have been calculated over the X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

1974
1974
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 2 publications
3
19
0
Order By: Relevance
“…This is only a few percent of f b, in agreement with the calculated and observed ratio f'~/f'~ of the imaginary parts (Hildebrandt et al, 1973). It can be concluded that although the present experiment does not give any definite value for the angle-dependent part of f', it gives an upper limit and this limit is so low that it rules out any speculations that there may be significant effects of this kind.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…This is only a few percent of f b, in agreement with the calculated and observed ratio f'~/f'~ of the imaginary parts (Hildebrandt et al, 1973). It can be concluded that although the present experiment does not give any definite value for the angle-dependent part of f', it gives an upper limit and this limit is so low that it rules out any speculations that there may be significant effects of this kind.…”
Section: Resultssupporting
confidence: 86%
“…H6nl-type calculations, which have been supported by measurements (Hildebrandt, Stephenson & Wagenfeld, 1973), suggest that f" depends only very slightly on sin O/h, in contrast to calculations, which show noticeable effects for both f' and J" (Hazell, 1975). Interferometric measurements give f' at zero angle, as do measurements of the critical angle or calculations from the absorption coefficient through the Kramers-Kronig relations (Bonse & Hartmann-Lotsch, 1984;Dreier, Rabe, Malzfeldt & Niemann, 1984;Hoyt, de Fontaine & Warburton, 1984).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Dispersion corrections and absorption were taken into account. The linear absorption coefficient/.t was taken to be 14.64cm -1 and a value for the ratio of the imaginary parts of the polarizabilities Xi(333)/xi(O) --0.6 was used (Hildebrandt, Stephenson & Wagenfeld, 1973). Initially, the intrinsic reflection curve was calculated and then the convolution of two identical curves was performed.…”
mentioning
confidence: 99%
“…To calculate the photoelectric-absorption contribution to the imaginary part of the polarizability one usually uses the multipole series (Hildebrandt, Stephenson & Wagenfeld, 1973). It is enough to retain only the dipole and quadrupole terms because the remaining terms are small; then we have Xi'(k, k~)= z?…”
Section: Formulation and Solution Of The Diffraction Problemmentioning
confidence: 99%